REPRODUCTIVE ASPECTS OF CULTURED HUMPBACK GROUPER (Cromileptes altivelis) FOR SUPPORTING SEED PRODUCTION - Sari Budi Moria Sembiring; John Harianto Hutapea; Ahmad Muzaki; Ida Komang Wardana; Ni Wayan Widya Astuti; Retno Andamari (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Humpback grouper (Cromileptes altivelis) has been successfully spawned in 2000 by IMRAD (Institute of Mariculture Research and Development) and there are already the third generation (F3) currently. The reproductive aspects need to be studied to support the success of seed production. Humpback grouper reared in floating cage (F1 and F3) had matured (gonad stage 4) while F2 fish reared in concrete tanks has spawned. Gonadal maturity stage of 38 fishes from first generation (F1) and 35 fishes from the third generation were observed in June 2013 and compared to gonadal maturity stage of 18 fishes from the second generation observed in June 2009. Samples were measured in total length and body weight and gonads were taken for histology preparation to determine gonadal maturity stage and the sex. From the histological observation of the gonads, it showed that all female humpback grouper were in early maturity stage (stage I and II) with gonadal maturity index between 0.12% and 5.45%. Further, it was observed that the same gonad was found in different maturity stage and concluded that humpback groupers were multiple spawners (asynchronous). By determining gonadal maturity level, it was also known the minimum size for grouper ready to spawn.